Quiz As an Innovative Approach in Teaching Community Medicine to Medical Students - Devi, K (National Journal of Community Medicine, 2014)
Research question: Whether Quiz method can serve as an alternative and innovative method to teach “International Health” for undergratuate medical students. Methods: Descriptive study was undertaken among 151 MBBS students in the Department of Commuity medicine, MAPIMS.A series of 4 sessionby quiz method was conducted to teach “ International health”. There were 4 teams in which5 students wereselected as participants. Pretest and post test was conducted to evaluate their performance and in addition feedback was elicited. Results:The performance of the students in quiz was encouraging with 2 teams scoring 100%. The average score in pretest and posttest was 33.3% and 98.6% respectively. The students appreciated the method as it was different from routine lectures, innovative, interesting, interactive, informative, helped them to come prepared and scope for participation. They suggested to have more quiz sessions for other topis as well. Conclusion: Quiz method was sucessfully used to teach “International Health” to under gratuate medical students.